A Comparative Study of Children's Literature in Pakistan: Traditional vs. AI-Generated Stories in Reader Engagement and Cultural Relevance - Faria Amjad; Ali Raza Siddique; Ammara Farukh (University of Chitral Journal of Linguistics and Literature, 2024)
The genre of Pakistani English short stories has been instrumental in shaping the identity of Pakistan and its people. With the rapid advancement of artificial intelligence (AI) in our digital society, there is a transformative impact on various aspects of life, including storytelling. This study delves into the evolving landscape of children's literature in Pakistan by conducting a comparative analysis between traditional short stories from Dawn Young World and AI-generated narratives tailored for young Pakistani readers. The research aims to explore the similarities and differences between these narratives using multidimensional analysis and qualitative analysis. The primary focus lies in understanding the impact of AI on storytelling for Pakistani children, specifically assessing potential variations in cultural relevance between narratives crafted by humans and those generated by AI. The study reveals significant differences in scores of dimensions 1 (involved vs. informational) between the two corpora through ANOVA followed by a mean comparison test. While AI technology demonstrates remarkable strides in emulating storytelling styles and producing involved and engaging narratives deemed superior to those by human authors, a qualitative analysis using the cultural continuum model indicates a shortfall in delivering the cultural relevance inherent in human-authored tales. The findings advocate for collaborative approaches that leverage AI's efficiency in producing linguistically rich text while preserving human creativity and societal context. The goal is to craft meaningful and culturally resonant storytelling experiences for young readers in Pakistan.